Allocations of Sunk Capacity Costs and Joint Costs in a Linear Principal-Agent Model - Hemmer, Thomas (The Accounting Review, 1996)
[Banker and Hughes (1994) demonstrate the economic sufficiency of normal activity-based unit cost for optimal pricing decisions. This paper provides an agency parallel to their analysis by examining how, in the presence of capacity costs, the desirable tradeoff between risk-sharing and incentives can be achieved through modification of the performance measures on which the contract is based. Similar to Banker and Hughes (1994), I find that the optimal capacity cost allocation is a function only of budgeted volume when capacity can be used to produce a single product. Analysis of a joint production setting, however, reveals the optimal allocation to be based on the joint products' estimated net realizable values.]